Legal Enforcement on the Misuse of Health Data in the SATUSEHAT Mobile Application: Patient Privacy Protection - Andreas Abimanyu Prasetya; Elvito Primanda Wibowo; Hendryco Bintang Burju Sianipar; Vita Surya Pratiwi (PT. Caesarindo Triloka Persada, 2026)
This study investigates the legal protection of patient privacy in Indonesia’s SATUSEHAT mobile application, which serves as a centralized platform for Electronic Medical Records (EMRs). As digital transformation in the healthcare sector accelerates, concerns over data security and privacy become increasingly urgent. Existing studies have highlighted regulatory efforts but often overlook the practical enforcement and institutional gaps, particularly in mobile health platforms. Using a normative juridical approach, this research analyzes legal texts, government regulations, and expert commentaries related to the Personal Data Protection Law, Health Law, and Ministry of Health Regulation No. 24 of 2022. The findings reveal that while a legal framework exists, there are major challenges in its implementation, including limited digital infrastructure, weak legal synchronization, low digital literacy among health workers, and the absence of robust monitoring mechanisms. A key contribution of this study is its comprehensive analysis of both legal and practical dimensions of data privacy, offering strategic recommendations to enhance regulation enforcement and institutional preparedness. By bridging the gap between regulation and on-ground realities, this research underscores the importance of an integrated, secure, and ethically responsible approach to digital health governance in Indonesia.